1982
DOI: 10.1037/0021-9010.67.6.784
|View full text |Cite
|
Sign up to set email alerts
|

Occupational stress among student nurses: A natural experiment.

Abstract: This article describes a natural experiment that overcomes a number of methodological problems inherent in previous studies of occupational stress and strengthens evidence for the causal role of the work setting in influencing mental health and well-being. Student nurses (N = 164) were randomly assigned to one of four possible combinations of ward types such that two factors-type of nursing (medical/surgical) and sex of patients (male/female)-were systematically varied with counterbalancing of order effects. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
100
0
7

Year Published

1982
1982
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(112 citation statements)
references
References 36 publications
5
100
0
7
Order By: Relevance
“…The study of student nurses by Parkes (1980aParkes ( , 1981 sheds considerable light on this point; because it is unusual in that the nurses were given the CFQ before entering into the stressful situation of working on hospital wards. It was found that wards differed in the degree of difficulty which they produced for the nurse; for example, a sample of 88 nurses who had each worked on medical and on surgical wards gave significantly different MHQ scores when they had spent the previous six weeks on medical wards than when they had been working on surgical wards.…”
Section: E Broadbent P F Cooper P Fitzgerald and K R Parkesmentioning
confidence: 99%
“…The study of student nurses by Parkes (1980aParkes ( , 1981 sheds considerable light on this point; because it is unusual in that the nurses were given the CFQ before entering into the stressful situation of working on hospital wards. It was found that wards differed in the degree of difficulty which they produced for the nurse; for example, a sample of 88 nurses who had each worked on medical and on surgical wards gave significantly different MHQ scores when they had spent the previous six weeks on medical wards than when they had been working on surgical wards.…”
Section: E Broadbent P F Cooper P Fitzgerald and K R Parkesmentioning
confidence: 99%
“…Une autre a trouvé une association entre ce type d'absence pour maladie et une faible latitude décisionnelle seulement (Houtman et al, 1994). Enfin, une autre n'a démontré aucune association entre ce type d'absence et un changement au niveau de la latitude, de la demande et du soutien social (Parkes, 1982 s'intéressait aux cols blancs. Chez ces derniers, la médiane de la distribution partageait les sujets exposés ou non exposés à une demande élevée ou à une latitude faible.…”
Section: Discussionunclassified
“…Un première mesure d'absence comprend l'ensemble des absences pour maladie quelle que soit la durée. Les études répertoriées qui ont mesuré l'association entre la tension au travail et l'absence pour maladie ont utilisé cette mesure (Dwyer et Ganster, 1991;Karasek, 1979;Kristensen, 1991;Parkes, 1982). Une deuxième mesure désigne l'ensemble des absences pour maladie néces-sitant un certificat médical, quel que soit le diagnostic.…”
Section: Variables Et Instruments De Mesureunclassified
See 1 more Smart Citation
“…It has been shown that an increase in perceived work support among nurses is associated with im proved work performance, as well as with increased job satisfaction (Parkes, 1982). A support group can be a forum for staff to identify behaviours that may be contributing to problem situations, such as ineffective commu nication patterns or unrealistic expectations of self, team members or administration (Guillory & Riggin, 1991).…”
mentioning
confidence: 99%